Inorganic Nitrogen Assimilation in Yeasts: Alteration in Enzyme Activities Associated with Changes in Cultural Conditions and Growth Phase - Thomulka, Kenneth W. (1972)
Ammonia assimilation has been investigated in four strains of Saccharomyces cerevisiae by measuring, at intervals throughout the growth cycle, the activities of several enzymes concerned with inorganic ammonia assimilation. Enzyme activities in extracts of cells were compared after growth in complete and defined media. The effect of shift from growth in a complete to growth in a defined medium (and the reverse) was also determined. The absence of aspartase (EC 4.3.1.1, l-aspartate-ammonia lyase) activity, the low specific activities of alanine dehydrogenase, glutamine synthetase [EC 6.3.1.2, l-glutamate-ammonia ligase (ADP)], and the marked increase in activity of the nicotinamide adenine dinucleotide phosphate-linked glutamate dehydrogenase (NADP-GDH) [EC 1.4.1.4, l-glutamate:NADP-oxidoreductase (deaminating)] during the early stages of growth support the conclusion that yeasts assimilate ammonia primarily via glutamate. The NADP-GDH showed a rapid increase in activity just before the initiation of exponential growth, reached a maximum at the mid-exponential stage, and then gradually declined in activity in the stationary phase. The NADP-GDH reached a higher level of activity when the yeasts were grown on the defined medium as compared with complete medium. The nicotinamide adenine dinucleotide-linked glutamate dehydrogenase (NAD-GDH) [EC 1.4.1.2, l-glutamate:NAD-oxidoreductase (deaminating)] showed only slight increases in activity during the exponential phase of growth. There was an inverse relationship in that the NADP-GDH increased in activity as the NAD-GDH decreased. The NAD-GDH activity was higher after growth on the complete medium. The glutamate-oxaloacetate transaminase (EC 2.6.1.1. l-aspartate:2-oxoglutarate aminotransferase) activity rose and fell in parallel with the NADP-GDH, although its specific activity was somewhat lower. Although other ammonia-assimilatory enzymes were demonstrable, it seems unlikely that their combined activities could account for the remainder of the ammonia-assimilatory capacity not accounted for by the NADP-GDH. The ability of aspartate to serve as effectively as glutamate as the sole source of nitrogen for the growth of yeast apparently resides in their ability to utilize aspartate for amino acid biosynthesis via transamination.